Soetomo Covid-19 Score As An Early Identification Tools of Covid-19 Patients in Surabaya, Indonesia - Vininsia Merry Laura Mesang, - (International Journal of Research Publications, 2021)
Background Clinical prediction scores support the assessment of patients to limit the COVID-19 outbreak. Soetomo COVID-19 Score (SCS) has been used to determine further diagnostic and patient zoning purposes in our hospital. We aimed to evaluate the SCS characteristics and its capability to determine those with COVID-19 infection. Methods The score was evaluated using retrospective analysis from March 2020 to January 2021, which was undertaken on patients who had taken SARS CoV-2 PCR swab at Dr. Soetomo General Hospital, Surabaya. Descriptive, Chi-Square, and Mann-Whitney tests were analysed to evaluate the comparison among PCR SARS CoV-2 swab results. Receiver operating characteristic was carried out to determine the SS discrimination capability. Results Of 454 subjects participating in the study, 32.8% of them were confirmed COVID-19. They had a lower leukocyte level and a higher median total of SCS (10010?9448 cells/mm3). Most of the SCS characteristics showed significant results according to the swab results. SCS had a good discrimination capacity (AUC 82.5%, 95% CI 78.2-86.8%; p<0.001). Total SCS 12.5 was the optimal cut-off point to discriminate suspected COVID-19 patients with good sensitivity (89.3%) and specificity (78.4%). Conclusions The newly developed SCS is a considerable tool for an early COVID-19 patients identification.